Five different pictures of the play 'Lenin. Tragödie einer Revolution in zwei Teilen' written by Ernst Fischer performed on stage at the Carl-theatre in Vienna and a 2-page letter by Molly Keizer-Prins, dated: Vienna autumn 1928, on this play (1928)
Five different pictures of the play 'Lenin. Tragödie einer Revolution in zwei Teilen' written by Ernst Fischer performed on stage at the Carl-theatre in Vienna and a 2-page letter by Molly Keizer-Prins, dated: Vienna autumn 1928, on this play.